The happiness revolution – a movement for positive mental health. - Chan, Li Chuen Agnessa Cassandra. (2012)
This paper presents the communication campaign “The Happiness Revolution”, a movement for positive mental well-being by four undergraduates from the Wee Kim Wee School of Communication. Targeted at tertiary students aged 18-25, this activity-based campaign aims to broaden perceptions of mental health through a focus on positive psychology theories and techniques, moving beyond an association with mental illness. This paper includes a summary of research that shaped key campaign strategies, outlines the crafting and creative execution of communication plans and campaign tactics, and presents an extensive evaluation of the campaign’s overall effectiveness based on both process and outcome measures.